2021
DOI: 10.3390/ijms22157978
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thylakoid Protein Phosphorylation in Energy-Dependent Quenching of Chlorophyll Fluorescence in Rice Plants

Abstract: Under natural environments, light quality and quantity are extremely varied. To respond and acclimate to such changes, plants have developed a multiplicity of molecular regulatory mechanisms. Non-photochemical quenching of chlorophyll fluorescence (NPQ) and thylakoid protein phosphorylation are two mechanisms that protect vascular plants. To clarify the role of thylakoid protein phosphorylation in energy-dependent quenching of chlorophyll fluorescence (qE) in rice plants, we used a direct Western blot assay af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 75 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…Therefore, the high photosynthetic production potential of WDR in severe drought would be fully understood by revealing the interaction mechanisms between g m and energy distribution in PSII and PSI system. Mesophyll cell structures including anatomical structure, ultrastructures of chloroplast and thylakoid membrane, and intracellular physiological traits such as aquaporins, carbonic anhydrase, and thylakoid membrane proteins and protein complexes have different functions and contribution pathways to regulate g m and energy distribution during responding to stress environment in rice plants (Flexas et al ., 2012; Xiong et al ., 2017; Wang et al ., 2018b; Pashayeva et al ., 2021; Wu et al ., 2021). However, it is still indistinct how the cell structures interacted with physiological functions regulate g m and energy distribution to maintaining high photosynthetic production ability in water stress in rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high photosynthetic production potential of WDR in severe drought would be fully understood by revealing the interaction mechanisms between g m and energy distribution in PSII and PSI system. Mesophyll cell structures including anatomical structure, ultrastructures of chloroplast and thylakoid membrane, and intracellular physiological traits such as aquaporins, carbonic anhydrase, and thylakoid membrane proteins and protein complexes have different functions and contribution pathways to regulate g m and energy distribution during responding to stress environment in rice plants (Flexas et al ., 2012; Xiong et al ., 2017; Wang et al ., 2018b; Pashayeva et al ., 2021; Wu et al ., 2021). However, it is still indistinct how the cell structures interacted with physiological functions regulate g m and energy distribution to maintaining high photosynthetic production ability in water stress in rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis is pivotal for plant growth and yield (Yang et al, 2014 ), and gene encoding photosynthetic enzymes play significant roles in photosynthesis and pigmentation (Pashayeva et al, 2021 ; Li et al, 2022b ). The KEGG results showed that photosynthesis and photosynthesis-antenna proteins were significantly enriched ( Figure 3C ).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, the Fv/Fm ratio that was measured in dark-adapted (20 min) leaves was found to decrease under MoDS in all cultivars, but to remain unaffected in the introgression line IL12-4 which decreased only under SDS (Figure 4a). However, the use of Fv/Fm as an efficient indicator has been frequently questioned [25,[74][75][76], and recently it was recommended that the Fv/Fm parameter must not to be related to the efficiency of PSII photochemistry [77,78]. In contrast, the pattern of the redox state of quinone A (Q A ) has been shown to be a good indicator to probe photosynthetic efficiency and to determine the impact of abiotic or biotic stress on photosynthesis [25,43,79].…”
Section: Discussionmentioning
confidence: 99%